Psychological Distress in Patients With Recurrent Ectopic Pregnancies: A Cross‐Sectional Study - Na‐Na Ren; Minerva B. De Ala; Ling Chang; Yuan Gao; Ming‐Xia Li; Ke‐Li Li (Nursing Open)
ABSTRACT Aim Most patients with ectopic pregnancies experience a high level of psychological distress for various reasons. The psychological state and needs of patients with recurrent ectopic pregnancies need to be seriously addressed. However, psychological distress in patients with recurrent ectopic pregnancy has not been widely studied. The purpose of this study is to investigate and understand the prevalence and factors influencing psychological distress in patients with recurrent ectopic pregnancies. Design A cross‐sectional study. Methods This study follows the STROBE guidelines. The Kessler Psychological Distress Scale (K10) was utilised to assess the level of psychological stress in patients. The Kruskal–Wallis test or Mann–Whitney U test was used to compare the factors influencing psychological stress in patients with different conditions. Results A total of 134 patients with recurrent ectopic pregnancies completed the survey, and most patients experienced moderate‐to‐severe psychological distress. The psychological distress experienced by patients with recurrent ectopic pregnancies is complex and dynamic, influenced by various factors. Among them, the main factors affecting the psychological distress of patients were age, education level, number of children, number of abortions, medical insurance and economic pressure (p < 0.05). Conclusion This study suggests that the psychological distress experienced by patients with recurrent ectopic pregnancies is universal and cannot be ignored. It is necessary to pay attention to the psychological needs of patients with recurrent ectopic pregnancies and carry out scientific and effective psychological care management.